A Survey on Vulnerabilities and Performance Evaluation Criteria in Blockchain Technology - Srivastav, Rishi Kumar; Agrawal, Devendra; Shrivastava, Anurag (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2020)
The blockchain technology firstly presented by Haber and Stornetta in the year 1990, and first time blockchain technology used in Bitcoin by Satoshi Nakamoto in 2008. The blockchain technology is truly decentralized technology. In blockchain technology, every block has consisted three main parts that is data, hash block, and the previous hash block. Hash is controls the uniqueness of each block and it is unique for each block. Each block also contains the hash of the previous block; thus, the blocks are connected to each other. A blockchain can divided into three categories public blockchain, consortium blockchain and private blockchain. The proposed paper provided the comparative and analytical review on the blockchain consensus algorithms.